Selected Physicochemical Properties of Diamond Like Carbon (DLC) Coating on Ti-13Nb-13Zr Alloy Used for Blood Contacting Implants - Magdalena Antonowicz (Materials, 2020)
Despite high interest in the issues of hemocompatibility of titanium implants, particularly those made of the Ti-13Nb-13Zr alloy, the applied methods of surface modification still do not always guarantee the physicochemical properties required for their safe operation. The factors that reduce the efficiency of the application of titanium alloys in the treatment of conditions of the cardiovascular system include blood coagulation and fibrous proliferation within the vessel’s internal walls. They result from their surfaces’ physicochemical properties not being fully adapted to the specifics of the circulatory system. Until now, the generation and development mechanics of these adverse processes are not fully known. Thus, the fundamental problem in this work is to determine the correlation between the physicochemical properties of the diamond like carbon (DLC) coating (shaped by the technological conditions of the process) applied onto the Ti-13Nb-13Zr alloy designed for contact with blood and its hemocompatibility. In the paper, microscopic metallographic, surface roughness, wettability, free surface energy, hardness, coating adhesion to the substrate, impendence, and potentiodynamic studies in artificial plasma were carried out. The surface layer with the DLC coating ensures the required surface roughness and hydrophobic character and sufficient pitting corrosion resistance in artificial plasma. On the other hand, the proposed CrN interlayer results in better adhesion of the coating to the Ti-13Nb-13Zr alloy. This type of coating is an alternative to the modification of titanium alloy surfaces using various elements to improve the blood environment’s hemocompatibility.